The Financial Performance of Aqad Shirkah: A case study of financial and non-financial institutions - Damanhur, .; Saputra, Jumadil; Falahuddin, . (Opción, 2019)
There is a recognized opportunity to generate profit from the intermediation between savers and investors or lenders and borrowers. This led to the growth of the conventional financial system. In contrast, Islamic institutions that fund business activities must comply with the Shariah. This study investigates the financial performance of the aqad Shirkah (joint venture). The result shows that the financial performance is categorized as very healthy. In contrast, BCA Commercial was unhealthy. It indicates that the Aqad Shirkah is more profitable compared to other financial systems.